Long-term survival benefits of intrathecal autologous bone marrow-derived mesenchymal stem cells (Neuronata-R®: lenzumestrocel) treatment in ALS: Propensity-score-matched control, surveillance study - Nam, Jae-Yong; Chun, Sehwan; Lee, Tae Yong; Seo, Yunjeong; Kim, Kwijoo; Park, Jinseok; Sung, Wonjae; Oh, Ki-Wook; Lee, Sanggon; Park, Jin-Sung; Oh, Juyeon; Chung, Kyung Cheon; et al. (Frontiers in Aging Neuroscience, 2023)
Objective Neuronata-R® (lenzumestrocel) is an autologous bone marrow-derived mesenchymal stem cell (BM-MSC) product, which was conditionally approved by the Korean Ministry of Food and Drug Safety (KMFDS, Republic of Korea) in 2013 for the treatment of amyotrophic lateral sclerosis (ALS). In the present study, we aimed to investigate the long-term survival benefits of treatment with intrathecal lenzumestrocel. Methods A total of 157 participants who received lenzumestrocel and whose symptom duration was less than 2 years were included in the analysis (BM-MSC group). The survival data of placebo participants from the Pooled-Resource Open-Access ALS Clinical Trials (PROACT) database were used as the external control, and propensity score matching (PSM) was used to reduce confounding biases in baseline characteristics. Adverse events were recorded during the entire follow-up period after the first treatment. Results Survival probability was significantly higher in the BM-MSC group compared to the external control group from the PROACT database (log-rank, p < 0.001). Multivariate Cox proportional hazard analysis showed a significantly lower hazard ratio for death in the BM-MSC group and indicated that multiple injections were more effective. Additionally, there were no serious adverse drug reactions found during the safety assessment, lasting a year after the first administration. Conclusion The results of the present study showed that lenzumestrocel treatment had a long-term survival benefit in real-world ALS patients.